2020
DOI: 10.1093/jas/skaa252
|View full text |Cite
|
Sign up to set email alerts
|

Supplementing a Saccharomyces cerevisiae fermentation product modulates innate immune function and ameliorates bovine respiratory syncytial virus infection in neonatal calves

Abstract: The objectives of this study were to determine the effects of oral supplementation with Saccharomyces cerevisiae fermentation products (SCFP; SmartCare and NutriTek; Diamond V, Cedar Rapids, IA) on immune function and bovine respiratory syncytial virus (BRSV) infection in preweaned dairy calves. Twenty-four Holstein x Angus, 1-2 day old calves (38.46 ± 0.91 kg initial body weight) were assigned two treatment groups: control; or SCFP treated, milk replacer with 1 g/d SCFP (SmartCare) and calf starter top-dresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 39 publications
6
42
0
Order By: Relevance
“…The period of six weeks in which feed was supplemented with SCFP did not result in an altered composition of circulating immune cells as at the day of vaccination both groups (PLA, OLI) did not differ significantly in any of the measured parameters ( Table 2 ). This is in line with findings in calves and lambs where the SCPF feeding had no influence on the fraction of circulating immune cells subpopulations [ 15 , 25 ]. In contrast, according to the literature, SCFP supplementation raised the numbers of circulating leukocytes and neutrophils in heat-stressed cows [ 26 ] and the fraction of monocytes and B-cells in adult dogs [ 9 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The period of six weeks in which feed was supplemented with SCFP did not result in an altered composition of circulating immune cells as at the day of vaccination both groups (PLA, OLI) did not differ significantly in any of the measured parameters ( Table 2 ). This is in line with findings in calves and lambs where the SCPF feeding had no influence on the fraction of circulating immune cells subpopulations [ 15 , 25 ]. In contrast, according to the literature, SCFP supplementation raised the numbers of circulating leukocytes and neutrophils in heat-stressed cows [ 26 ] and the fraction of monocytes and B-cells in adult dogs [ 9 ].…”
Section: Discussionsupporting
confidence: 92%
“…In adult cows, SCFP supplementation (20–90 g/animal/day for up to 60 days) altered the phenotype of circulating neutrophilic granulocytes, their phagocytosing capacity, and the gene expression of circulating leukocytes [ 13 , 14 ]. In calves, SCFP supplementation (1–5 g/day/animal) modulated both systemic and mucosal immune responses, resulting in reduced lung pathology, and a reduced incidence of secondary bacterial infection [ 15 ]. In beef calves challenged intravenously with LPS, SCFP-fed animals (12 g/day for 21 days) showed a reduced acute phase response and lower serum TNF levels [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The current experimental approach also intended to maintain each BSI explant and its individual microbiome under conditions reflecting physioxic oxygen conditions of 5% O 2 (Note: 1-10% O 2 is commonly found in the small intestinal lumen of mammalian hosts [29]). As an interesting finding, SEM analyses showed parasite-driven hole-like lesions in the epithelial surfaces of parasitized villi, as reported for both in vitro experiments with permanent host cells [13] and in vivo lesions in C. parvum-infected bovine small intestines [41,42].…”
Section: Cryptosporidium Parvum Replication In Bsi Explants Under Physioxic Oxygen Conditionssupporting
confidence: 77%
“…Saccharomyces cerevisiae fermentation products ( SCFP ) have positive effects on many aspects of immune function in cattle, swine, poultry, and humans ( Moyad et al, 2009 ; Shen et al, 2011 ; Brewer et al, 2014 ; Alugongo et al, 2017 ). In a previous study, we observed that supplementation with SCFP modulated innate immune function in preweaned calves ( Mahmoud et al, 2020 ). Immune cells isolated from the blood of SCFP-fed calves had an increased capacity for proinflammatory cytokine production, whereas immune cells isolated from the lungs produced fewer proinflammatory cytokines ( Mahmoud et al, 2020 ).…”
Section: Introductionmentioning
confidence: 91%
“…Immune cells isolated from the blood of SCFP-fed calves had an increased capacity for proinflammatory cytokine production, whereas immune cells isolated from the lungs produced fewer proinflammatory cytokines ( Mahmoud et al, 2020 ). Subsequently, calves receiving SCFP developed less clinical disease and less lung pathology following an experimental bovine respiratory syncytial viral ( BRSV ) infection ( Mahmoud et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%